190 Complement Membrane Attack Complex (MAC) Level in CSF Provides Rapid Identification of Shunt Infection and Failure. (August 2015) - Johnston, James M.; Ramos, Theresa N.; Arynchyna, Anastasia A.; Blackburn, Tessa E.; Amburgy, John; Rocque, Brandon George; Blount, Jeffrey P.; Rozzelle, Curtis J.; Oakes, Jerry; Barnum, Scott R.
Abstract : INTRODUCTION: Shunt infection and failure are associated with significant medical costs and hospitalization days. Current practice relies on microbiology culture, which significantly delays definitive diagnosis. Complement activation in the cerebrospinal fluid (CSF) has been shown to be a reliable biomarker of meningitis but has not been evaluated in shunt infection or failure. A rapid diagnostic complement assay could aid in identifying patients with hydrocephalus-associated complications. METHODS: A prospective cohort of 40 pediatric neurosurgical patients with newly diagnosed hydrocephalus, shunt failure, or shunt infection were enrolled from November 2014 through February 2015 at a single tertiary-care children's hospital. CSF was acquired at the time of initial surgical intervention and, in cases of infection, serial CSF draws were performed. Complement membrane attack complex (MAC) levels in 108 CSF samples were measured by ELISA. Statistical analysis was performed using GraphPad Prism to correlate MAC levels with culture-proven CSF infection. RESULTS: Of 40 patients, median age was 4 years (range 0-23). Etiologies of hydrocephalus included intraventricular hemorrhage, myelomeningocele, congenital hydrocephalus and tumor. Three statistically distinct categories of CSF MAC levels were identified: (1) pyogenic infection (1581 ± 1218 ng/mL, mean ± SEM); (2) symptomatic ventricular enlargement (SVE) without infection (39.2 ± 8.9 ng/mL); and (3) asymptomatic/ Propionibacterium acnes infection (undetectable MAC < 3.7 ng/mL at 1:7 dilution). Infected patients had significantly higher MAC levels compared with SVE patients (Mann-Whitney, P = .003). In addition, infected patients undergoing serial CSF draws demonstrated progressive decrease in MAC levels over the course of antibiotic treatment. CONCLUSION: Preliminary results show CSF MAC levels may help differentiate between pyogenic infection, symptomatic ventricular enlargement, and asymptomatic/ P acnes infected children. We are currently expanding this study with respect to patient number and complement biomarkers to establish predictive values that facilitate clinical decision making in this challenging population.